Pengaruh Pemilihan Gaya Pangkas Rambut Untuk Rambut Keriting Pria - nadiya nur fakhira; Maulina, A'ida; Nurjannah, Tasya (Journal of Beauty and Cosmetology (JBC), 2025)
This study aims to explore the impact of hairstyle selection on self-image, self-esteem, and comfort among men with curly hair. The research employs a qualitative approach with in-depth interviews as the primary method of data collection. The sample consists of 20 men with curly hair, selected through purposive sampling. Data analysis is conducted using thematic analysis to identify recurring patterns and themes related to hairstyle choices and their psychological effects. The findings reveal that men with curly hair often face challenges in choosing hairstyles that align with societal beauty standards while also expressing their identity. They tend to favor structured and symmetrical hairstyles to fit social norms but also explore more natural styles to assert individuality. However, dissatisfaction with stylist skills in handling curly hair remains a significant issue. The study highlights the need for increased education and training for hairstylists to better accommodate the needs of curly-haired individuals. The findings contribute to the understanding of how hairstyle choices affect self-perception among men with curly hair and emphasize the importance of inclusivity in hairdressing services. Keywords: curly hair, hairstyle choices, self-esteem, self-image, hairstyling, men